PEMBERIAN TRICHOKOMPOS JERAMI JAGUNG DAN PUPUK UREAPERTUMBUHAN DAN PRODUKSI TANAMAN KAILAN(Brassica oleracea Var. alboglabra) - Satria, Ielham Ekha; Yetti, Husna; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to determine effect of tricho compos made from corn waste combined with urea on the growth and production of kailan (Brassica oleracea var. alboglabra). This research was conducted on April 2015 until May 2015 in the experimental garden in Agriculture faculty of University of Riau, Panam, Pekanbaru. Research was conducted experimentally using Randomized Block Design (RBD) factorial. Each treatment was repeated 3 times to obtain 36 experimental units. Each experimental unit consisted of 10 plants and five plants was taken as a sample plants. The first factor consists of 3 levels, were: tricho compos 1 kg/plot, tricho compos 2 kg/plot and tricho compos 3 kg/plot. The second factor is Urea fertilizer consists of 4 levels, were: 0 g/plot, 5 g/plot, 7,5 g/plot and 10 g/plot. Oberserved parameters were the plant height, leafes number, and fresh plant weight. Data were analyzed by ANOVA and further tested using Duncan`s New Multiple Range Test (DNMRT) at the level of 5%. The results shows giving tricho compos of corn waste and urea influenced on the plant height and fresh plant weight. Giving tricho compos of corn waste with dose of   2 kg/plot and urea 5 g/plot is the best dose in enhancing growth and production of kailan   Keywords: trichokompos, kailan, urea